PENGARUH PARTISIPASI MASYARAKAT, KOMPETENSI APARATUR DESA DAN TRANSPARANSI TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA DI KECAMATAN GATAK KABUPATEN SUKOHARJO - Subadi Subadi; Wikan Budi Utami; Rukmini Rukmini (Jurnal Akuntansi dan Pajak, 2023)
The research purpose was analyzed the effect of community participation, competence of village government officials, and transparency on the accountability of managing village funds in Gatak District, Sukoharjo Regency. The research type is quantitative research with primary data sources. The samples were community members (members of the BPD) and employees who worked in 14 village offices in Gatak District, Sukoharjo Regency, totaling 98 people. The sampling technique is purposive sampling technique. Data collection techniques used survey techniques by distributing questionnaires. The data analysis method used Multiple Linear Regression using the SPSS test tool. The hypothesis testing method used the t test, F test, and the coefficient of determination (R2). The results showed that community participation and competence of village government officials had a positive and significant effect on village fund management accountability in Gatak District, Sukoharjo Regency. Transparency has not significant effect on the accountability of managing village funds in Gatak District, Sukoharjo Regency. Community participation, competence of village government officials, and transparency are able to explain village fund management accountability by 35.6%, the remaining 64.4% is explained by other factors not explained in the regression model. Keywords : Village funds, accountability, community participation, competence, transparency.